Profile control particle as well as preparation method and application thereof

By performing copolymerization of the skeleton monomer, charged monomer and complex monomer in the skeleton particles and supramolecular complexing with inorganic metal ions, nanoscale skeleton particles with core-shell structure were prepared, and the skeleton was solved. The problem of weak mechanical strength of the section particles after expansion achieves both high mechanical strength and high expansion.

CN119431659AActive Publication Date: 2025-02-14CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411403598.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-14
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The mechanical strength of existing section granules weakens or even breaks after water absorption and expansion, making it difficult to adapt to complex reservoir environments, and it is difficult to have both high expansion multiples and high mechanical strength.

Method used

By copolymerizing hydrophilic skeleton monomer, highly absorbent charged monomer and supramolecular complexing monomer and supramolecular complexing monomer and supramolecular complexing with inorganic metal ions (such as zirconium ions), a copolymer with a core-shell structure is formed Particles, nanoscale diaphragm particles are prepared by combining phacoemulsification and high-speed dispersion.

Benefits of technology

The regulating particles maintain high mechanical strength during the expansion process and have good shear resistance of formations. It solves the problem of weak mechanical strength of traditional regulating particles after expansion, and can go deep into the reservoir for effective regulating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431659A_ABST
    Figure CN119431659A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of petroleum exploration and development, and discloses a profile control particle and a preparation method and application thereof, the profile control particle comprises a copolymer and inorganic metal ions complexed on the copolymer, the copolymer comprises a first structural unit provided by a skeleton monomer, a second structural unit provided by a charged monomer and a third structural unit provided by a complexing monomer, and the inorganic metal ions are zirconium ions; the profile control particle has slow expansibility and high mechanical strength, and can realize deep profile control of a reservoir in an oil reservoir.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of petroleum exploration and development, and in particular to a profile control particle and a preparation method and application thereof. Background Art

[0002] Oilfield production can be divided into primary oil production (self-flowing oil production) relying on natural elastic energy, secondary oil production relying on water injection to supplement energy, tertiary oil production relying on chemical agents, and the fourth or even fifth oil production stage to further improve the recovery rate after tertiary oil production. Primary oil production can generally only produce 5-20% of the original geological reserves of oil; after the secondary water drive production, generally 20-40% of the original geological reserves of oil are produced; complex reservoirs with high water content still have more than 30% residual oil that cannot be produced after chemical agent tertiary oil production. At the same time, the heterogeneity of the reservoir and long-term water injection will lead to the development of internal dominant channels, "short circuit" of active oil displacement agents, reduced oil production, and increased oil production costs. In order to solve the "short circuit" problem and further improve oil production efficiency, it is a current research hotspot to inject body expansion particles into water injection wells to block the dominant crossflow channels and adjust the flow profile. Deep profile control of oil reservoirs requires profile control particles to have high mechanical strength, high expansion, and injectability. Polymer gel particles, mainly cross-linked polyacrylamide, can absorb water and swell to block the high permeability area after being injected into the high permeability area of ​​the reservoir, thereby forcing the flow to turn. It is a very effective means of profile control. However, due to size limitations and expansion along the way during continuous injection, conventional gel particles are prone to blockage of the entrance and cannot enter the deep part of the reservoir. In addition, the mechanical strength of highly expanded gel particles is reduced or even broken, making it difficult to adapt to complex reservoir environments. Increasing the cross-linking agent concentration in the gel particle synthetic material is an effective way to improve its mechanical strength, but the introduction of high-concentration cross-linking agents will lead to a decrease in the expansion multiple.

[0003] Therefore, high expansion multiple and high mechanical strength after expansion are two properties that are difficult for gel particles to have at the same time. It is of great significance to study and develop a preparation method for nano-profile control particles with both expansion and mechanical properties to solve the problems of "cannot be injected", "cannot travel far", "cannot be blocked" and "low strength" of profile control particles. Summary of the invention

[0004] The purpose of the present invention is to overcome the defect problem of gel particles (profile control particles) in the prior art that the mechanical strength is weakened or even broken after absorbing water and swelling, and to provide a profile control particle and a preparation method and application thereof. The profile control particle has both slow expansion and high mechanical strength, and can achieve deep profile control of reservoirs in oil reservoirs.

[0005] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a profile-adjusting particle, wherein the profile-adjusting particle includes a copolymer and an inorganic metal ion complexed on the copolymer, wherein the copolymer includes a first structural unit provided by a backbone monomer, a second structural unit provided by a charged monomer and a third structural unit provided by a complexing monomer, and the inorganic metal ion is a zirconium ion.

[0006] A second aspect of the present invention provides a method for preparing the aforementioned profile-controlled particles, wherein the preparation method comprises: (1) contacting a backbone monomer, a charged monomer, a complexing monomer, a salt containing an inorganic metal ion, an initiator, a cross-linking agent, and water to prepare a dispersed phase; (2) contacting a surfactant and an organic solvent to prepare a continuous phase; (3) adding the dispersed phase to the continuous phase under ultrasonic conditions to obtain a water-in-oil emulsion; (4) The water-in-oil emulsion is heated to carry out a free radical polymerization reaction, and then washed, centrifuged, and dried to obtain profile-adjusted particles.

[0007] A third aspect of the present invention provides a use of the above-mentioned profile control particles as a profile control agent in an oil reservoir.

[0008] Through the above technical scheme, the present invention achieves high expandability while maintaining a certain mechanical strength by copolymerizing hydrophilic skeleton monomers, highly absorbent charged monomers, and supramolecular complex monomers and metal supramolecular complexation, and has good formation shear resistance, thereby solving the problem that traditional profile control particles have weak mechanical strength or even breakage after expansion. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 is a TEM image of profile-controlled particles with a core-shell structure prepared by a one-step method in Example 1 of the present invention; Figure 2 is an enlarged TEM image of the profile-controlled particles with a core-shell structure prepared by the one-step method in Example 1 of the present invention; Figure 3 It is a schematic diagram of the expansion ratios at different zirconium (Zr) concentrations in Comparative Example 1 and Examples 2-6 of the present invention; Figure 4 It is a schematic diagram of the effect of different zirconium addition amounts on the mechanical strength performance after expansion for 7 days in Comparative Example 1 and Examples 2-6 of the present invention; Figure 5 It is a schematic diagram of the effect of different Ac concentrations on water absorption and swelling properties in Example 5, Example 7 and Example 8 of the present invention; Figure 6 It is a schematic diagram of the effect of different Ac concentrations on mechanical strength after expansion for 7 days in Example 5, Example 7 and Example 8 of the present invention; Figure 7 It is a schematic diagram of the effect of the amount of complexing monomer added on the water absorption and swelling properties in Examples 6, 9 and 10 of the present invention; Figure 8 It is a schematic diagram of the effect of the amount of complexing monomer added on the mechanical strength of Example 6, Example 9, and Example 10 of the present invention. DETAILED DESCRIPTION

[0010] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0011] As described above, the first aspect of the present invention provides a profile-adjusting particle, wherein the profile-adjusting particle includes a copolymer and an inorganic metal ion complexed on the copolymer, wherein the copolymer includes a first structural unit provided by a backbone monomer, a second structural unit provided by a charged monomer, and a third structural unit provided by a complexing monomer, and the inorganic metal ion is a zirconium ion.

[0012] The inventors of the present invention have discovered that by copolymerizing (hydrophilic) skeleton monomers, (highly absorbent) charged monomers, and (supramolecular) complexing monomers and complexing inorganic metal ions (metal supramolecular), high expandability can be achieved while maintaining a certain mechanical strength, thereby having good formation shear resistance, and solving the problem of weak mechanical strength or even breakage of traditional profile control particles after expansion.

[0013] Furthermore, by adjusting the content of metal ions and complexing monomers, the particle expansion and mechanical strength can be controlled; in addition, the method of combining ultrasonic emulsification with high-speed dispersion can directly prepare nano-sized particles without the need to mechanically crush large pieces of gel, thus better suited for deep reservoir profile control.

[0014] According to the present invention, the backbone monomer is acrylamide.

[0015] According to the present invention, the charged monomer includes one or more of 2-acrylamide-2-methylpropanesulfonic acid, sodium p-styrenesulfonate, (3-acrylamidepropyl)trimethylammonium chloride and acryloyloxyethyltrimethylammonium chloride.

[0016] According to the present invention, the complexing monomer includes one or more of acrylic acid, methacrylic acid, maleic acid, itaconic acid and aconitic acid having a carboxyl group.

[0017] According to the present invention, based on the total structural units of the copolymer, the content of the first structural unit is 30-80wt%, the content of the second structural unit is 10-50wt%, and the content of the third structural unit is 1-30wt%; According to the present invention, preferably, based on the total structural units of the copolymer, the content of the first structural unit is 45-67.1wt%, the content of the second structural unit is 20.9-49.3wt%, and the content of the third structural unit is 5.7-21.8wt%. In the present invention, the first structural unit, the second structural unit and the third structural unit form a covalently cross-linked copolymer through a free radical reaction.

[0018] According to the present invention, based on the total content of the copolymer, the content of the inorganic metal ion is 1-30wt%, preferably 3.8-18.9wt%. In the present invention, the supramolecular complex monomer and the inorganic metal ion form an ion complex through supramolecular complexation.

[0019] According to the present invention, the particle size of the profile-controlled particles is less than 1 um, preferably 90-100 nm, more preferably 100 nm, by combining ultrasonic emulsification and stirring dispersion, rather than crushing the bulk gel by mechanical methods.

[0020] According to the present invention, the profile control particles have slow expansion properties, and the expansion ratio of the profile control particles is ≤83.

[0021] According to the present invention, the compressive strength of the profile control particles after swelling in salt water for 7 days can reach up to 0.99 MPa, that is, the compressive strength is ≤0.99 MPa.

[0022] A second aspect of the present invention provides a method for preparing the aforementioned profile-controlled particles, wherein the preparation method comprises: (1) contacting a backbone monomer, a charged monomer, a complexing monomer, a salt containing an inorganic metal ion, an initiator, a cross-linking agent, and water to prepare a dispersed phase; (2) contacting a surfactant and an organic solvent to prepare a continuous phase; (3) adding the dispersed phase to the continuous phase under ultrasonic conditions to obtain a water-in-oil emulsion; (4) The water-in-oil emulsion is heated to carry out a free radical polymerization reaction, and then washed, centrifuged, and dried to obtain profile-adjusted particles.

[0023] According to the present invention, the amount of each material used includes, in terms of molar equivalents: 0.001-0.1M of the skeleton monomer, 0.0001-0.1M of the charged monomer, 0.0001-0.1M of the complexing monomer, 0.00001-0.001M of the salt containing inorganic metal ions, and 1×10 -5 Up to 1×10 -3 M; preferably, the backbone monomer is 0.01-0.1M, the charged monomer is 0.001-0.003M, the complexing monomer is 0.001-0.003M, the salt of the inorganic metal ion is 0.0002-0.0007M, and the crosslinking agent is 1×10 -4 M to 1×10 -3 M, initiator is 1×10 -4 M to 1×10 -3 M.

[0024] According to the present invention, the surfactant is Span80.

[0025] According to the present invention, the organic solvent is selected from one or more of cyclohexane, chloroform, n-hexane, dichloromethane, toluene and ethyl acetate.

[0026] According to the present invention, the salt containing inorganic metal ions is selected from one or more of zirconium oxychloride, zirconium acetate, zirconium sulfate, zirconium chloride, zirconium silicate and zirconium hydroxide.

[0027] According to the present invention, the crosslinking agent is N,N-methylenebisacrylamide.

[0028] According to the present invention, the initiator is ammonium persulfate.

[0029] According to the present invention, in step (3), ultrasonic dispersion is performed by a cell disruptor for 3-5 minutes, preferably for 5 minutes.

[0030] According to the present invention, in step (4), the conditions of the free radical polymerization reaction include: temperature of 50-80°C, time of 60-300 min; preferably, temperature of 65-75°C, time of 80-180 min; more preferably, heating at 70°C for 90 min. Preferably, the free radical polymerization reaction is carried out under stirring conditions, and the stirring speed is 500-1200 rpm / min, preferably 1000 rpm / min.

[0031] According to the present invention, in step (4), the centrifugal rate is 5000-7000 rpm / min, and the centrifugal time is 5-10 min. Preferably, the centrifugal rate is 6000-6500 rpm / min, and the centrifugal time is 5-7 min. In addition, the process can be repeated 3-5 times, preferably 3 times.

[0032] According to the present invention, the reactant after step (4) is dried in an oven at 50-60° C. for 24-30 hours.

[0033] According to a particularly preferred embodiment of the present invention, a method for preparing profile-controlled particles comprises: (a) adding a hydrophilic backbone monomer, a highly water-absorbent charged monomer, a supramolecular complexing monomer, a salt containing an inorganic metal ion, a crosslinking agent and an initiator into water to prepare a dispersed phase; (b) adding a surfactant to a water-insoluble organic solvent to prepare a continuous phase; (c) adding the mixture of step (a) to the mixture of step (b) to obtain a layered mixture, and dispersing the mixture by ultrasonication to obtain a stable water-in-oil emulsion; (d) performing free radical polymerization reaction in step (c) in a high temperature water bath with high speed stirring until the reaction is complete; (e) washing the product from step (d) with a large amount of ethanol; (f) centrifugation; (g) repeating the washing-centrifugation process; (h) Dry and set aside.

[0034] Results Nano-profile-controlled particles with both expandability and high mechanical strength were prepared.

[0035] A third aspect of the present invention provides a use of the above-mentioned profile control particles as a profile control agent in an oil reservoir.

[0036] According to the present invention, the conditions applicable to the oil reservoir include: a temperature of 30-80°C, a mineralization of 0.1×10 4 mg / L to 1×10 4 mg / L.

[0037] The present invention will be described in detail below through examples.

[0038] In the following examples and comparative examples: The expansion ratio is calculated by the following formula. s is the weight of the gel after expansion, W d The mass of the gel after drying.

[0039]

[0040] Mechanical strength (Stress) is obtained through compression testing at a measurement rate of 5 mm / min.

[0041] In the present invention, it should be noted that the mechanical strength is the mechanical strength measured at the end of expansion.

[0042] Unless otherwise specified, all raw materials were analytical grade reagents purchased from Aladdin Reagent Co., Ltd.

[0043] Example 1 This embodiment is intended to illustrate the profile-controlled particles prepared by the method of the present invention.

[0044] The raw materials include: hydrophilic skeleton monomer acrylamide, metal supramolecular complex monomer acrylic acid (Ac), charged monomer 2-acrylamide-2-methylpropanesulfonic acid (Amps), conventional cross-linking agent N,N-methylenebisacrylamide, salt containing inorganic metal ions (metal supramolecular complex cross-linking agent) is zirconium acetate, and free radical reaction initiator ammonium persulfate.

[0045] Preparation method: (1) Acrylamide 0.008M, acrylic acid 0.001M, 2-acrylamide-2-methylpropanesulfonic acid 0.001M, N,N-methylenebisacrylamide (0.1%M of total monomers), zirconium acetate 0.0004M, N,N-methylenebisacrylamide 1×10 -3 M, ammonium persulfate 2×10 -3 M, dissolved in 1g water and stirred thoroughly to dissolve; (2) Span80 (0.4 g) was dissolved in 10 g cyclohexane and stirred thoroughly; (3) Add (1) to (2) and sonicate for 5 minutes; (4) Place on a magnetic stirrer, 1000 rpm / min, and heat in a 70°C water bath for 90 min; (5) Add a large amount of ethanol to wash and centrifuge (centrifugal speed is 6000 rpm / min, centrifugal time is 5 min), and repeat 3 times; (6) Dry in an oven at 50°C for 24 hours.

[0046] The prepared nanogel particles, i.e., profile-adjusted particles, have a first structural unit content of 67.1 wt%, a second structural unit content of 24.4 wt%, and a third structural unit content of 8.5 wt% based on the total structural units of the copolymer; in addition, the inorganic metal ion content is 11 wt% based on the total content of the copolymer.

[0047] Figure 1 is a TEM image of the profile-controlled particles prepared in Example 1 of the present invention; Figure 2 is a TEM image of the profile-controlled particles with a core-shell structure prepared by the one-step method in Example 1 of the present invention; Figure 1 and Figure 2 It can be seen that the particle size (diameter) of the profile-controlled particles prepared in the embodiment is less than 100 nm and the particles are nanogel particles with a core-shell structure.

[0048] Comparative Example 1 This embodiment is intended to illustrate the profile-controlled particles prepared by the method of the present invention.

[0049] The raw materials include: acrylamide as a skeleton hydrophilic monomer, acrylic acid as a metal supramolecular complex monomer, 2-acrylamide-2-methylpropanesulfonic acid as a charged monomer, N,N-methylenebisacrylamide as a crosslinking agent, and ammonium persulfate as a free radical reaction initiator. In this comparative example 1, the preparation raw materials do not include zirconium acetate, a salt containing inorganic metal ions (metal supramolecular complex crosslinking agent).

[0050] Preparation method: (1) Acrylamide 0.008M, acrylic acid 0.001M, 2-acrylamide-2-methylpropanesulfonic acid 0.001M, zirconium acetate 0, N,N-methylenebisacrylamide 1×10 -3 M, ammonium persulfate 2×10 -3 M, dissolve in 1g water and stir thoroughly to dissolve.

[0051] (2) Span80 (0.4 g) was dissolved in 10 g cyclohexane and stirred thoroughly; (3) Add (1) to (2) and sonicate for 5 minutes; (4) Place on a magnetic stirrer, 1000 rpm / min, and heat in a 70°C water bath for 90 min; (5) Add a large amount of ethanol to wash and centrifuge (centrifugal speed is 6000 rpm / min, centrifugal time is 5 min), and repeat 3 times; (6) Dry in an oven at 50°C for 24 hours.

[0052] The prepared nanogel particles, i.e., profile-adjusted particles, have a first structural unit content of 67.1 wt%, a second structural unit content of 24.4 wt%, and a third structural unit content of 8.5 wt% based on the total structural units of the copolymer; in addition, the inorganic metal ion content is 0 based on the total content of the copolymer.

[0053] Example 2 This embodiment is intended to illustrate the profile-controlled particles prepared by the method of the present invention.

[0054] The profile-controlled particles were prepared in the same manner as in Example 1, except that the "zirconium acetate 0.0004 M" in Example 1 was changed to "zirconium oxychloride 0.0001 M".

[0055] The prepared nanogel particles, i.e., profile-adjusted particles, have a first structural unit content of 67.1 wt%, a second structural unit content of 24.4 wt%, and a third structural unit content of 8.5 wt% based on the total structural units of the copolymer; in addition, the inorganic metal ion content is 3.8 wt% based on the total content of the copolymer.

[0056] Example 3 This embodiment is intended to illustrate the profile-controlled particles prepared by the method of the present invention.

[0057] The profile-controlled particles were prepared in the same manner as in Example 1, except that the "zirconium acetate 0.0004 M" in Example 1 was changed to "zirconium oxychloride 0.0002 M".

[0058] The prepared nanogel particles, i.e., profile-adjusted particles, have a first structural unit content of 67.1 wt%, a second structural unit content of 24.4 wt%, and a third structural unit content of 8.5 wt% based on the total structural units of the copolymer; in addition, the inorganic metal ion content is 7.6 wt% based on the total content of the copolymer.

[0059] Example 4 This embodiment is intended to illustrate the profile-controlled particles prepared by the method of the present invention.

[0060] The profile-controlled particles were prepared in the same manner as in Example 1, except that the "zirconium acetate 0.0004 M" in Example 1 was changed to "zirconium oxychloride 0.0003 M".

[0061] The prepared nanogel particles, i.e., profile-adjusted particles, have a first structural unit content of 67.1 wt%, a second structural unit content of 24.4 wt%, and a third structural unit content of 8.5 wt% based on the total structural units of the copolymer; in addition, the inorganic metal ion content is 11.3 wt% based on the total content of the copolymer.

[0062] Example 5 This embodiment is intended to illustrate the profile-controlled particles prepared by the method of the present invention.

[0063] The profile-controlled particles were prepared in the same manner as in Example 1, except that the “zirconium acetate 0.0004 M” in Example 1 was changed to “zirconium oxychloride 0.0004 M”.

[0064] The prepared nanogel particles, i.e., profile-adjusted particles, have a first structural unit content of 67.1 wt%, a second structural unit content of 24.4 wt%, and a third structural unit content of 8.5 wt% based on the total structural units of the copolymer; in addition, the inorganic metal ion content is 15.1 wt% based on the total content of the copolymer.

[0065] Example 6 This embodiment is intended to illustrate the profile-controlled particles prepared by the method of the present invention.

[0066] The profile-controlled particles were prepared in the same manner as in Example 1, except that the “zirconium acetate 0.0004 M” in Example 1 was changed to “zirconium oxychloride (0.0005 M)”.

[0067] The prepared nanogel particles, i.e., profile-adjusted particles, have a content of 67.1 wt% of the first structural unit, 24.4 wt% of the second structural unit, and 8.5 wt% of the third structural unit based on the total structural units of the copolymer; in addition, the content of the inorganic metal ions is 18.9 wt% based on the total content of the copolymer.

[0068] Example 7 This embodiment is intended to illustrate the profile-controlled particles prepared by the method of the present invention.

[0069] Profile-controlled particles were prepared in the same manner as in Example 1, except that "0.001 M acrylic acid" in Example 1 was changed to "0.002 M acrylic acid", and "zirconium acetate" in Example 1 was changed to "zirconium oxychloride".

[0070] The prepared nanogel particles, i.e., profile-adjusted particles, have a first structural unit content of 61.8 wt%, a second structural unit content of 22.5 wt%, and a third structural unit content of 15.7 wt% based on the total structural units of the copolymer; in addition, a content of the inorganic metal ions is 13.9 wt% based on the total content of the copolymer.

[0071] Example 8 This embodiment is intended to illustrate the profile-controlled particles prepared by the method of the present invention.

[0072] The profile-controlled particles were prepared in the same manner as in Example 1, except that the "acrylic acid 0.001 M" in Example 1 was changed to "acrylic acid 0.003 M", and the "zirconium acetate" in Example 1 was changed to "zirconium oxychloride".

[0073] The prepared nanogel particles, i.e., profile-adjusted particles, have a first structural unit content of 57.3 wt%, a second structural unit content of 20.9 wt%, and a third structural unit content of 21.8 wt% based on the total structural units of the copolymer; in addition, the inorganic metal ion content is 12.9% based on the total content of the copolymer. Example 9 This embodiment is intended to illustrate the profile-controlled particles prepared by the method of the present invention.

[0074] Profile-controlled particles were prepared in the same manner as in Example 5, except that the “2-acrylamide-2-methylpropanesulfonic acid 0.001 M” in Example 5 was changed to “2-acrylamide-2-methylpropanesulfonic acid 0.002 M”.

[0075] The prepared nanogel particles, i.e., profile-adjusted particles, have a first structural unit content of 53.9 wt%, a second structural unit content of 39.3 wt%, and a third structural unit content of 6.8 wt% based on the total structural units of the copolymer; in addition, a content of the inorganic metal ions is 12.1 wt% based on the total content of the copolymer.

[0076] Example 10 Profile-controlled particles were prepared in the same manner as in Example 9, except that the “2-acrylamide-2-methylpropanesulfonic acid 0.002 M” in Example 9 was changed to “2-acrylamide-2-methylpropanesulfonic acid 0.003 M”.

[0077] The prepared nanogel particles, i.e., profile-adjusted particles, have a first structural unit content of 45 wt%, a second structural unit content of 49.3 wt%, and a third structural unit content of 5.7 wt% based on the total structural units of the copolymer; in addition, a content of the inorganic metal ions is 10.2 wt% based on the total content of the copolymer.

[0078] By comparing the Figure 1 and Figure 2 It can be seen that the particle size of the prepared profile control particles can reach the nanometer level, and the minimum can be less than 100 nm, which can solve the problem of "injection failure" of profile control particles and meet the injectability of profile control particles in deep oil reservoirs. At the same time, nanoparticles with a core-shell structure can be prepared in one step.

[0079] By comparing Comparative Example 1, Examples 2 to 6 and Figure 3 and Figure 4It can be seen that by increasing the content of metal complex ion zirconium, the expansion performance of the gel is slightly weakened, and the mechanical strength is greatly enhanced. When the zirconium concentration is 0.0004M, the mechanical strength is the highest. When the expansion ratio is 46, the mechanical strength can reach 0.51MPa. However, if the zirconium content continues to increase, the mechanical strength will decrease.

[0080] By comparing Example 5, Example 7 and Example 8 and Figure 5 and Figure 6 It can be seen that increasing the content of acrylic acid in the complexing monomer can enhance the complexing effect between the systems, and the mechanical strength of the gel is significantly improved. After seven days of expansion (expansion ratio of 15.7), the mechanical strength can reach up to 0.89MPa; however, the expansion performance is significantly weakened. Therefore, in order to ensure the expansion performance during application, it is necessary to carefully increase the complexing effect in the system.

[0081] By comparing Example 6, Example 9 and Example 10 and Figure 7 and Figure 8 It can be seen that increasing the content of the charged monomer 2-acrylamide-2-methylpropanesulfonic acid can significantly enhance the expansion performance of the gel system, and the expansion ratio can reach up to 115. However, at ultra-high expansion ratios, the mechanical strength is also weakened accordingly.

[0082] It can be seen from the above results that the present invention connects the hydrophilic skeleton monomer, the highly absorbent charged monomer, and the supramolecular complex monomer with covalent bonds through free radical reactions to form a copolymer, and at the same time adds metal ions to form physical crosslinks through metal supramolecular complexation. The expansibility and mechanical strength can be adjusted by adjusting the components of different monomers, thereby realizing the preparation of particles with both expansibility and mechanical strength, having good formation shear resistance, and solving the problem that traditional profile control particles have weak mechanical strength or even breakage after expansion.

[0083] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A profile-controlled particle, characterized in that: The profile-adjusting particles include a copolymer and an inorganic metal ion complexed on the copolymer, wherein the copolymer includes a first structural unit provided by a skeleton monomer, a second structural unit provided by a charged monomer and a third structural unit provided by a complexing monomer, and the inorganic metal ion is a zirconium ion.

2. The profile-modified particles according to claim 1, wherein: The backbone monomer is acrylamide; And / or, the charged monomer includes one or more of 2-acrylamide-2-methylpropanesulfonic acid, sodium p-styrenesulfonate, (3-acrylamidepropyl)trimethylammonium chloride and acryloyloxyethyltrimethylammonium chloride; And / or, the complexing monomer includes one or more of acrylic acid, methacrylic acid, maleic acid, itaconic acid and aconitic acid.

3. The profile-controlled particles according to claim 1 or 2, wherein: Based on the total structural units of the copolymer, the content of the first structural unit is 30-80wt%, the content of the second structural unit is 10-50wt%, and the content of the third structural unit is 1-30wt%; Preferably, based on the total structural units of the copolymer, the content of the first structural unit is 45-67.1wt%, the content of the second structural unit is 20.9-49.3wt%, and the content of the third structural unit is 5.7-21.8wt%.

4. The profile-modified particles according to claim 1 or 2, wherein: Based on the total content of the copolymer, the content of the inorganic metal ion is 1-30 wt %, preferably 3.8-18.9 wt %.

5. The profile-modified particles according to any one of claims 1 to 4, wherein: The particle size of the profile-controlled particles is ≤1 um, preferably 90-100 nm; And / or, the profile control particles have slow expansion properties, and the expansion ratio of the profile control particles is ≤83; And / or, the compressive strength of the profile control particles after swelling in salt water for 7 days is ≤0.99 MPa.

6. A method for preparing profile-controlled particles according to any one of claims 1 to 5, characterized in that: The preparation method comprises: (1) contacting a backbone monomer, a charged monomer, a complexing monomer, a salt containing an inorganic metal ion, an initiator, a cross-linking agent, and water to prepare a dispersed phase; (2) contacting a surfactant and an organic solvent to prepare a continuous phase; (3) adding the dispersed phase to the continuous phase under ultrasonic conditions to obtain a water-in-oil emulsion; (4) The water-in-oil emulsion is heated to carry out a free radical polymerization reaction, and then washed, centrifuged, and dried to obtain profile-adjusted particles.

7. The preparation method according to claim 6, wherein: In terms of molar equivalent, the amount of each material includes: The skeleton monomer is 0.001-0.1M, the charged monomer is 0.0001-0.1M, the complexing monomer is 0.0001-0.1M, the salt of inorganic metal ions is 0.00001-0.001M, and the cross-linking agent is 1×10 -5 M to 1×10 -3 M, initiator is 1×10 -5 M to 1×10 -3 M; Preferably, the backbone monomer is 0.01-0.1M, the charged monomer is 0.001-0.003M, the complexing monomer is 0.001-0.003M, the salt of the inorganic metal ion is 0.0002-0.0007M, and the crosslinking agent is 1×10 -4 M to 1×10 -3 M, initiator is 1×10 -4 M to 1×10 -3 M.

8. The preparation method according to claim 6, wherein: The organic solvent is selected from one or more of cyclohexane, chloroform, n-hexane, dichloromethane, toluene and ethyl acetate; And / or, the salt containing inorganic metal ions is selected from one or more of zirconium oxychloride, zirconium acetate, zirconium sulfate, zirconium chloride, zirconium silicate and zirconium hydroxide.

9. The preparation method according to claim 6, wherein: The conditions of the free radical polymerization reaction include: temperature of 50-80°C and time of 60-300min; Preferably, the temperature is 65-75°C and the time is 80-180 min.

10. Use of the profile control particle according to any one of claims 1 to 5 as a profile control agent in an oil reservoir.

Citation Information

Patent Citations

  • Strength-controllable profile control water shutoff agent, preparation method, strength identification method and application

    CN117986452A

  • Preformed particle gel for conformance control in an oil reservoir

    US20070204989A1

  • Delayed crosslinking agents for high-temperature fracturing

    US20100048430A1

  • Swellable polymer with anionic sites

    US20100314114A1

  • Polyampholytes-high temperature polymers and method of use

    US4959163A